Answer:
Therefore the solution of the differential equation is
[tex]ye^{4x^3} = 3e^{4x^3}+c[/tex] [ where c is arbitrary constant]
Step-by-step explanation:
Given differential equation is
[tex]\frac{dy}{dx} +12x^2y= 36x^2[/tex]
Here [tex]P(x)= 12x^2[/tex] and [tex]Q(x) = 36 x^2[/tex]
The integrating factor of the differential equation is
[tex]= e^{\int P(x) dx[/tex]
[tex]=e^{\int 12x^2dx[/tex]
[tex]=e^{ \frac{12x^3}{3}}[/tex]
[tex]=e^{4x^3}[/tex]
Multiplying the integrating factor both sides of the differential equation
[tex]e^{4x^3}\frac{dy}{dx} +12x^2ye^{4x^3}= 36x^2e^{4x^3}[/tex]
[tex]\Rightarrow e^{4x^3} dy+12x^2ye^{4x^3}dx= 36x^2e^{4x^3}dx[/tex]
Integrating both sides,
[tex]\int e^{4x^3} dy+\int12x^2ye^{4x^3}dx= \int36x^2e^{4x^3}dx[/tex]......(1)
Let
[tex]I= \int36x^2e^{4x^3}dx[/tex]
[tex]= \int3. 12 x^2e^{4x^3}dx[/tex]
putting [tex]{4x^3}=z[/tex] , [tex]12x^2 dx=dz[/tex]
[tex]=\int 3. e^zdz[/tex]
[tex]=3e^z+c[/tex] [ where c is arbitrary constant]
Putting the value of z
[tex]=3e^{4x^3}+c[/tex]
From (1) we get
[tex]\int e^{4x^3} dy+\int12x^2ye^{4x^3}dx= \int36x^2e^{4x^3}dx[/tex]
[tex]\Rightarrow ye^{4x^3} = 3e^{4x^3}+c[/tex]
Therefore the solution of the differential equation is
[tex]ye^{4x^3} = 3e^{4x^3}+c[/tex] [ where c is arbitrary constant]